2023
DOI: 10.1038/s41467-023-41458-5
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate change, population growth, and power sector decarbonization on urban building energy use

Chenghao Wang,
Jiyun Song,
Dachuan Shi
et al.

Abstract: Climate, technologies, and socio-economic changes will influence future building energy use in cities. However, current low-resolution regional and state-level analyses are insufficient to reliably assist city-level decision-making. Here we estimate mid-century hourly building energy consumption in 277 U.S. urban areas using a bottom-up approach. The projected future climate change results in heterogeneous changes in energy use intensity (EUI) among urban areas, particularly under higher warming scenarios, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…4C ), measures to encourage reduced consumption could be the best option for reducing gas-related emissions. In relation to the climate warming scenarios from the Coupled Model Intercomparison Project Phase 6 ( 30 ), it is suggested that in urban areas, a 1°C warming could lead to a 10.5% reduction in building natural gas consumption, primarily for space heating purposes ( 31 ). Building energy efficiency policies could take this into account to create more effective and sustainable solutions.…”
Section: Discussionmentioning
confidence: 99%
“…4C ), measures to encourage reduced consumption could be the best option for reducing gas-related emissions. In relation to the climate warming scenarios from the Coupled Model Intercomparison Project Phase 6 ( 30 ), it is suggested that in urban areas, a 1°C warming could lead to a 10.5% reduction in building natural gas consumption, primarily for space heating purposes ( 31 ). Building energy efficiency policies could take this into account to create more effective and sustainable solutions.…”
Section: Discussionmentioning
confidence: 99%
“…16 Second, existing research exhibits limitations in data collection and model validation, often failing to adequately address the complexities of practical applications. 17 Third, current studies on decarbonization pathways, while assessing the economic and environmental benefits of heat pump technology, do not sufficiently delve into the impact of heat pump integration with other energy technologies, 18 particularly in combined heating and cooling supply scenarios.…”
Section: Interdisciplinary Research Effortsmentioning
confidence: 99%
“…The 7.4% increase was the lowest increase observed since 1930 (U.S. Census Bureau 2021). There are significant gaps in our understanding of cityscale impacts of population growth on electricity demand under a changing climate (Wang 2023). Increases in the efficiency of electric devices and appliances have partially offset the impact of population growth in U.S. energy consumption.…”
Section: Energy Grid and Water Interdependencies Supply Gapmentioning
confidence: 99%